Academic Enterpreneurship Behavior: The Case of Public Universities in Malaysia - Saad, Natrah; Ariffin, Zaimah Zainol (International Journal of Economics and Financial Issues, 2016)
This paper examines the academic behaviour of public universities in conducting enterpreneurship education from the perspectives of academicians. For that purpose, questionnaires were adopted following Llano modified Theory of Planned Behaviour (2010). The questionnaires were administered to three (3) public universities. Data gathered was analysed using Partial Least Squares (PLS) regression analysis. Results suggest that perceived desirability, attitude and university climate have significant influence on enterpreneurship education behavior in universities. In practice, the findings are expected to provide significant input to the public universities on their current enterpreneurship education behaviour and the necessary efforts to be undertaken in order to promote the enterpreneurship skills among graduates. In addition, the findings also add to the existing literature on enterpreneurship education particularly in Malaysian environment. Keywords: Enterpreneurship Education; Public Universities; Malaysia JEL Classifications: H8; I23; I28